Podpora lokalnega prebivalstva izvajanju naravovarstvenih ukrepov v območjih Natura 2000 poplavnih gozdov Mure - Plevnik, Kaja (Gozdarski vestnik, 2021)
The Mura River is incorporated in the Natura 2000 areas network in its entire river flow; however, parts of this area are in unfavorable conservation status, which is a consequence of the past hydromeliorational measures, water pollution, and forest cutting for gaining new agricultural areas. With the public opinion survey among the population of ten towns in the surroundings of the Gornja Bistrica and Murska šuma pilot areas (June-July 2015; N = 303), we wanted to determine knowledge of diverse nature protection regimes, understanding the restrictions for the landowners, opinion about human pressure on riparian forests, and the support for four protection measures for improving the conservation status of forest habitat types in both pilot areas. We discovered a relatively good knowledge of the special regime management areas, general approval on the importance of the restrictions in these areas, and majority belief that they do not considerably or highly limit the landowners, and that the riparian forests along Mura are neither distinctly exposed nor non-exposed to the pressures of society. Based on the support for protection measures – (1) removal of the non-native invasive species; (2) planting willow and alder in otter and beaver habitats; (3) establishing native tree species stands; (4) increasing the quantity of the dead tree biomass in the saproxylic beetle habitats – we could classify the interviewees into three classes with diverse preferences for performing the measures. In all three classes, the interviewees expressed positive preferences for a larger surface of the native tree species stands, in one of them for the removal of invasive species, and in one of them for establishing a stable saproxylic beetle population status. In two classes, they expressed negative preferences for increasing the otter and beaver populations and, at the same time, for removing invasive species. The most surprising is the findings that the interviewees were more inclined to the stabilization of the saproxylic beetle populations than for the increase of the otter and beaver populations. A possible explanation for this is also the fact that beaver and otter can cause damage to people (otter by fishing, beaver by causing damage on agricultural produce and trees).
Keywords: lokalno prebivalstvo; Mura (reka); naravovarstveni ukrepi; Natura 2000; poplavni gozd